Hungary : Corporate Governance Country Assessment - World Bank (Washington, DC, 2013)
This report assesses the corporate governance policy framework and enforcement and compliance practices in Hungary. Hungary has already invested considerable resources in upgrading its legislation to meet European Union Directives, and the legislative and regulatory framework dealing with corporate governance issues is robust. The major issues identified by this review include: (1) the general weakness of the supervisory board, which causes some non-compliance with several OECD Principles; and (2) a conflict between law and practice in the area of share registration, particularly the problems related to the ability of all shareholders to attend meetings and exercise their voting and other rights. Strengths and weaknesses are highlighted, and the policy recommendations made may be grouped under three categories: legislative reform, institutional strengthening, and voluntary/private initiatives. The report recommends creating a "share registration working group" to synchronize law and practice in the area of shareholder record keeping and voting. It also makes recommendations to be implemented as part of a Company Law update. Finally, the report promotes private sector initiatives and capacity building to build on legislative progress on corporate governance reform. It recommends developing a Hungarian corporate governance code of best practice, which would address key issues to include supervisory board roles and institutional investor responsibilities. The report also proposes that an Institute of Directors be created train supervisory board members, disseminate best practice, and promote dialogue between the public and private sectors. Together, these measures give issuers the choice to implement best practice and investors a benchmark against which to measure corporate governance in Hungary.